Institutional long-term care and government regulation - Elena Stancanelli (IZA World of Labor, 2015)
The demand for institutional long-term care is likely to remain high in OECD countries, because of longer life expectancy and falling cohabitation rates of the elderly with family members. As shortages of qualified nurses put a cap on the supply of beds at nursing homes, excess demand builds. That puts upward pressure on prices, which may not reflect the quality of the services that are provided. Monitoring the quality of nursing home services is high on the agenda of OECD governments. Enlisting feedback from family visitors and introducing portable benefits might improve quality at little extra cost.
Keywords: I13; J14; J18; 330; demography; family; long-term care